2004
DOI: 10.1124/mol.65.4.897
|View full text |Cite
|
Sign up to set email alerts
|

GlutathioneS-Transferase M1 and Multidrug Resistance Protein 1 Act in Synergy to Protect Melanoma Cells from Vincristine Effects

Abstract: Previous studies have shown that glutathione S-transferases (GSTs) can operate in synergy with efflux transporters, multidrug resistance proteins (MRPs), to confer resistance to several carcinogens, mutagens and anticancer drugs. To address the poorly documented role of the GSTM1 in cancer chemoresistance, we used CAL1 human melanoma cells expressing no endogenous GSTM1 and a high level of MRP1. Cells were transfected with an expression vector containing the GSTM1 cDNA, and different clones were selected expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 26 publications
1
37
0
2
Order By: Relevance
“…25,26 Glutathione S-transferases operate in synergy with specific proteins to confer a multidrug resistance to the melanoma and nonmelanoma tumor cells. 27,28 The GST-isoform is likely to make adducts with anticancer drugs and facilitate their transport outside the cells 29,30 ; GST-nuclear amount does not depend on the cytoplasmic level. 31 Low nuclear GST-expression seems to confirm indirectly that ATM is a morphologically distinct entity that can be distinguished from conventional melanomas.…”
Section: Commentmentioning
confidence: 99%
“…25,26 Glutathione S-transferases operate in synergy with specific proteins to confer a multidrug resistance to the melanoma and nonmelanoma tumor cells. 27,28 The GST-isoform is likely to make adducts with anticancer drugs and facilitate their transport outside the cells 29,30 ; GST-nuclear amount does not depend on the cytoplasmic level. 31 Low nuclear GST-expression seems to confirm indirectly that ATM is a morphologically distinct entity that can be distinguished from conventional melanomas.…”
Section: Commentmentioning
confidence: 99%
“…One study suggested that increased expression of GSTA1 is primarily responsible for acquired drug resistance (30), whereas other studies have suggested that GSTP1 and GSTM1 are responsible for drug resistance (32,33). Horton et al (34) showed a near-linear correlation between resistance to a bifunctional alkylating agent and overexpression of the A class of GSTs and suggested that overexpression of the GSTMs may be responsible for the observed resistance of ovarian carcinoma cells to bifunctional alkylating agents.…”
Section: Discussionmentioning
confidence: 99%
“…GSTs might mediate the development of MDR via direct detoxification and as an inhibitor of the MAP kinase pathway. Up-regulation of GSTs has been reported in several cancer types (12) including melanoma cells which were resistant to vincristine (13). Moreover, a reversal of these effects was also seen after the usage of GST inhibitors like dicumarol or curcumin (13).…”
Section: Introductionmentioning
confidence: 91%
“…Up-regulation of GSTs has been reported in several cancer types (12) including melanoma cells which were resistant to vincristine (13). Moreover, a reversal of these effects was also seen after the usage of GST inhibitors like dicumarol or curcumin (13). Therefore, a broad range of GST inhibitors were developed to modulate drug resistance and to sensitize tumor cells to cytotoxic drugs (11,14).…”
Section: Introductionmentioning
confidence: 99%